Gains and challenges with the Classroom Assessment Scoring System in a social pedagogical tradition - Evertsen, Cecilie; Størksen, Ingunn; Tharaldsen, Kjersti Balle; Kucirkova, Natalia (Frontiers in Education, 2023)
This qualitative study explores how Early Childhood Education and Care (ECEC) professionals’ perceptions of gains and challenges using the Classroom Assessment Scoring System (CLASS, Pre-K and Toddler) within the social pedagogical tradition in Norwegian ECEC. Focus group interviews (n = 22), group interviews (n = 4), and in-depth interviews (n = 3) were conducted online, followed by conventional content analysis. The findings indicate that ECEC professionals perceived CLASS as contributing to their pedagogical understanding and practice. At the same time, the introduction of CLASS enhanced ECEC professionals’ awareness regarding the pedagogical value of the social pedagogical tradition (SPT), which they wished to preserve and protect, and the specific elements of the school readiness tradition (SRT), which they wished to include in their pedagogical understanding of high-quality ECEC pedagogy. The findings suggest that the use of CLASS expands ECEC professionals’ understanding of the value of both pedagogical traditions. Finally, inspired by the present study’s findings regarding interaction quality, the research team proposes a hybrid model of pedagogical approaches in ECEC.